2004
DOI: 10.1016/j.aop.2004.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The world according to Rényi: thermodynamics of multifractal systems

Abstract: We discuss a basic thermodynamic properties of systems with multifractal structure. This is possible by extending the notion of Gibbs-Shannon's entropy into more general framework -Rényi's information entropy. We show a connection of Rényi's parameter q with the multifractal singularity spectrum f (α) and clarify a relationship with the Tsallis-Havrda-Charvat entropy. Finally, we generalize Hagedorn's statistical theory and apply it to high-energy particle collisions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
310
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(310 citation statements)
references
References 43 publications
0
310
0
Order By: Relevance
“…It should be noted how P. Jizba and T.Arimitsu (5) showed that Rényi's measure can be obtained also extending the Shannon-Khinchin axioms to a quasi-linear conditional information 12) with f as given in 1.10.…”
Section: Rényi's Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted how P. Jizba and T.Arimitsu (5) showed that Rényi's measure can be obtained also extending the Shannon-Khinchin axioms to a quasi-linear conditional information 12) with f as given in 1.10.…”
Section: Rényi's Entropymentioning
confidence: 99%
“…Its inverse is the generalized q-exponential function 5) which becomes the exponential function for q = 1. The importance of the q-logarithm is that it satisfies a pseudo-additive law log q xy = log q x + log q y + (1 − q)(log q x)(log q y) .…”
Section: Tsallis' Entropymentioning
confidence: 99%
“…In fact, when entropies I q or S q are used, it is necessary to know them for all q in order to obtain a full information on a given statistical system [35]. For ensuing applications in strange attractors the reader may consult Ref.…”
Section: For a Givenmentioning
confidence: 99%
“…Typical examples are provided by chaotic dynamical systems and multifractal statistical systems (see e.g., [35] and citations therein). Fully developed turbulence, earthquake analysis and generalized dimensions of strange attractors provide examples.…”
Section: Rény's Entropy: Entropy Of Multifractal Systemsmentioning
confidence: 99%
“…Napier's logarithm assures additivity while (18) imposes the exponential average. It should be noted how P. Jizba and T.Arimitsu [18] showed that Renyi's measure can be obtained also from the extension of the Shannon-Khinchin axioms [19] to a quasi-linear conditional information…”
Section: How To Construct Generalized Kn-averaged Information-entropymentioning
confidence: 99%